Implementation of remote control device using USB 1208LS - KARAARSLAN, K.; ÖZER, Tolga (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
In parallel with developments in technology, home automation systems arebeing increasingly used. In this study, computer networks and the power systemcan be controlled by Internet for a remote device. This application was carriedout in two stages of software and hardware. The software is developed in C #programming language. This software is connected to the computer usinga remote server devices, performed the required information has been sent. The second part of the application is prepared in the hardware. The information thatcome to the server Usb can handled and performed by Usb 1208LS. This circuitdesign performed and connected to the server Usb. After the coming data hasbeen processed, target device which connected to the circuit making power controland commands sent to the device peaks and the application process has beencompleted the desired